Wearable Sensors for Remote Health Monitoring: Potential Applications for Early Diagnosis of Covid‐19. Issue 1 (3rd September 2021) - Mirjalali, Sheyda; Peng, Shuhua; Fang, Zhijian; Wang, Chun‐Hui; Wu, Shuying
Abstract: Wearable sensors are emerging as a new technology to detect physiological and biochemical markers for remote health monitoring. By measuring vital signs such as respiratory rate, body temperature, and blood oxygen level, wearable sensors offer tremendous potential for the noninvasive and early diagnosis of numerous diseases such as Covid‐19. Over the past decade, significant progress has been made to develop wearable sensors with high sensitivity, accuracy, flexibility, and stretchability, bringing to reality a new paradigm of remote health monitoring. In this review paper, the latest advances in wearable sensor systems that can measure vital signs at an accuracy level matching those of point‐of‐care tests are presented. In particular, the focus of this review is placed on wearable sensors for measuring respiratory behavior, body temperature, and blood oxygen level, which are identified as the critical signals for diagnosing and monitoring Covid‐19. Various designs based on different materials and working mechanisms are summarized. This review is concluded by identifying the remaining challenges and future opportunities for this emerging field. Abstract : Wearable sensors have demonstrated grand potential for remote health monitoring recently, particularly after the Covid‐19 pandemic. The need for wearable telehealth systems capable of monitoring vital signs, such as respiratory rate, body temperature, and blood oxygen level has surged. In this review, the recent advances in creating these sensors and remaining challenges as well as prospects are presented.